(untitled) (Bangladesh Journal of Urology, 2020)
Objective: In this study, we aimed at making a comparison between the laparoscopic nephrectomy and open nephrectomy in terms of post-operative pain and pethidine consumption. Methods: The study has been designed with patients who underwent prospective and randomized laparoscopic and open nephrectomy operation. We assessed the post-operative pain through visual analogue scale (VAS) at the 0st, 2nd, 4th, 8th, 12th, 18th, and 24th post-operative hours. We carefully recorded the intraoperative and post-operative results along with the post-operative pain-relieving analgesic doses. Results: A total number of 30 patients were included in this study. The VAS scores of the two groups did not demonstrate a significant difference, but the analgesic (Pethidine) requirement was significantly lower in the laparoscopic group (p=0.031). The groups demonstrated no difference in terms of adverse effects. Conclusion: Along with similar perioperative results, laparoscopic nephrectomy offers an advantage in case of post-operative pain with regard to analgesic requirement and hospital stay duration. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.31-35